2022
DOI: 10.1093/biolre/ioac066
|View full text |Cite
|
Sign up to set email alerts
|

Paternal obesity induces placental hypoxia and sex-specific impairments in placental vascularization and offspring metabolism

Abstract: Paternal obesity predisposes offspring to metabolic dysfunction, but the underlying mechanisms remain unclear. We investigated whether this metabolic dysfunction is associated with changes in placental vascular development and is fueled by endoplasmic reticulum (ER) stress-mediated changes in fetal hepatic development. We also determined whether paternal obesity indirectly affects the in utero environment by disrupting maternal metabolic adaptations to pregnancy. Male mice fed a standard chow or high fat diet … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(22 citation statements)
references
References 66 publications
5
17
0
Order By: Relevance
“…A deconvolution analysis revealed changes in the placental lineage specification comparable with pathological changes observed in placental defects that are associated with adult-onset cardiometabolic diseases (Aliee & Theis, 2021; Chu et al, 2019a; Cuffe et al, 2014; Han et al, 2018). Comparative analysis between placental transcriptomic profiles from our paternal HFD-induced obesity model with that of a hypoxia-induced fetal growth restriction model, revealed common placental defects across the two models (Chu et al, 2019a) consistent with our previous work that sire-obesity induces placental hypoxia (Jazwiec et al, 2022). This study revealed that paternal obesity was linked with transcriptomic and cellular defects in the placenta and may drive developmental origins of cardiometabolic disease in offspring.…”
Section: Introductionsupporting
confidence: 88%
See 4 more Smart Citations
“…A deconvolution analysis revealed changes in the placental lineage specification comparable with pathological changes observed in placental defects that are associated with adult-onset cardiometabolic diseases (Aliee & Theis, 2021; Chu et al, 2019a; Cuffe et al, 2014; Han et al, 2018). Comparative analysis between placental transcriptomic profiles from our paternal HFD-induced obesity model with that of a hypoxia-induced fetal growth restriction model, revealed common placental defects across the two models (Chu et al, 2019a) consistent with our previous work that sire-obesity induces placental hypoxia (Jazwiec et al, 2022). This study revealed that paternal obesity was linked with transcriptomic and cellular defects in the placenta and may drive developmental origins of cardiometabolic disease in offspring.…”
Section: Introductionsupporting
confidence: 88%
“…It is therefore likely that the differential expression of imprinted genes detected in female and male placentas as a result of paternal obesity could at least partly explain metabolic phenotypes observed in this mouse model (Jazwiec et al, 2022;Pepin et al, 2022). We identified changes in sperm H3K4me3 associated with paternal obesity, some of which were enriched for transcription factor binding sites.…”
Section: Discussionmentioning
confidence: 84%
See 3 more Smart Citations